In cammino verso un mosaico per la rinascita della montagna abruzzese. Soggetti, settori produttivi e forme di ricostruzione socioeconomica - Ciccozzi, Enrico; Cerasoli, Domenico (Scienze del Territorio, 2018)
This paper presents a few experiences implemented in Media Valle dell’Aterno (near L’Aquila) after the 2009 earthquake. Once described the identity characters of the context, it tells how, over the recent years, visions contrasting the dominant centre-periphery development model are emerging, and an opposite geography takes shape originating from a recognition of territorial value. In particular, we focus on experiences that return to agriculture its dual function of producing goods and reproducing cultural values, highlighting how such experiences are creating a sort of coordination tool apt to put naturalistic tourism within a large socio-economic scenario connected to territorial resources.